A mixed-methods study to inform the clarity and accuracy of cannabis-use and cannabis-tobacco co-use survey measures - Watkins, Shannon Lea (Drug Alcohol Depend, 2021)
BACKGROUND: Legalization of medical and recreational cannabis in US states has been accompanied by increases in availability, acceptability, and diversity in methods of cannabis use, as well as an increase in devices and methods for cannabis-tobacco co-use. Updated and specific survey measures of cannabis and cannabis-tobacco co-use are needed. METHODS: We employed a mixed-methods approach to identify sources of specification and measurement error in cannabis and cannabis-tobacco co-use measures. We surveyed and interviewed 36 young adult (age 18–29) cannabis and tobacco co-users in California (2017–2018), triangulated with document analysis of online cannabis websites and forums. We investigated how survey reports of cannabis use and cannabis-tobacco co-use compare to narrative descriptions provided during in-depth interviews. We identify key strategies for researchers collecting self-reported survey data to enhance accuracy and comprehensiveness of measures. FINDINGS: Potential sources of survey error included: broad variation in cannabinoid content and concentration, inconsistent interpretation of questions between participants and researchers (e.g. blunts were not considered co-use), and substantial variation in dosage within and between products. No evidence of survey recall bias or response editing was detected. CONCLUSION: To enhance survey accuracy, we recommend surveys specify which cannabis delivery methods and forms are included and excluded in each measure, differentiate between cannabis products, and explicitly include or exclude CBD product use.